OK, after help from here, I tried 4 more questions and thought i got the hang of this. Now i have another dilemma. :S
By expressing: tan(alpha + beta) = sin(alpha + beta) / cos(alpha + beta)
Prove that: tan(alpha + beta) = tan alpha + tan beta / 1 - tan alpha tan beta
Here are my first steps:
= sin(alpha + beta) / cos(alpha + beta)
= sin alpha cos beta + cos alpha sin beta / cos alpha cos beta - sin alpha sin beta
now im stuck,
should i cancel out the cos and sin from top and bottom?
i tried that, but that didn't work. after i thought, since i was lookin for tan in my answer, i would sin / cos = tan
that also did not work out.... (or maybe i did something wrong)
please guide me.